Sırrı Rahile Hanım ve Divanı - Açıl, Berat. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
The main purpose of this thesis is to present the Turkish Divan by Sırri Rahile Hanım who lived in the nineteenth century. This study will establish the text of Divan, dwell on its form, content and style with some information about RahiIe Hanım's life, and her literary personality. Apart from these purposes, another important aim of this study is to analyze the "Mystical Concepts" used by Sırri in her Divan. Sırri was from Diyarbakır and lived there through most of her life. She lived in Baghdad for a while and then came to istanbul where she died. In the present work, Divan is examined in terms of its form, content and style. In terms of form, statistical information is provided about poetry forms, meter, and rhyme. The content is studied in three parts, religious and historical-mythological elements and the "Mystical Concepts" which are examined separately. For the fIrst part, the use of God, prophets, Qoranic verses, hadiths and religious personalities by Sırri in her Divan is examined. For the second part brief information about historical mythological elements are given and their use in the Divan specifIed. Lastly, we take up the "Mystical Concepts", since Sırri is a mystical (mutasawwıf) poet and uses these concepts, largely in her Divan. In the conclusion we present our general opinion about Sırri's life, her Divan and the "Mystical Concepts". At the end of this thesis an index of names used in the transcribed text, an index relevant to the analyses part and a copy of the text of the Divan are appended.
Keywords: Turkish poetry -- History and criticism.; Turkish literature -- History and criticism.